STRATEGI KOMUNIKASI PARISADA HINDU DHARMA INDONESIA ( PHDI) DALAM PEMBINAAN UMAT HINDU DI KOTA KENDARI TAHUN 2020-2021 - Widi Astuti; Ni Made Yuliani; I Nyoman Sueca (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
Provides guidance to Hindus is Parisada Hindu Dharma Indonesia, Kendari City. Parisada Hindu Dharma Indonesia or commonly abbreviated as PHDI is the highest assembly of Hindu religious institutions, which was established to serve Hindus in increasing Sraddha and Bhakti based on the Vedic Scriptures, as well as managing and developing Hindus in enhancing their awareness of religious life. Based on this background, researchers are interested in researching the "Communication Strategy of Parisada Hindu Dharma Indonesia in the Development of Hindus in Kendari City in 2020-2021", with the formulation of the problem, namely 1) What is the communication strategy of Parisada Hindu Dharma Indonesia in fostering Hindus in Kendari City in 2020-2021? 2) What are the inhibiting factors and supporting factors for the communication of Parisada Hindu Dharma Indonesia in fostering Hindus in Kendari City in 2020- 2021? 3) What are the implications of the communication of Parisada Hindu Dharma Indonesia in fostering Hindus in Kendari City in 2020-2021?.The theory used in this research is the theory of therapeutic communication, the theory of symbolic interactionism, and the theory of behaviorism. This study uses a qualitative approach. This type of data collection is qualitative from primary and secondary data sources. Data collection techniques used are observation, interviews, documentation. The research findings are: 1). The communication strategy implemented by PHDI Kendari City in coaching to increase Sraddha and Bhakti Hindus in Kendari City are public communication, persuasive communication, and direct communication 2) factors that become obstacles and support for PHDI in the coaching process, namely the presence of internal and external factors 3 ) The implications/impacts resulting from the coaching carried out by PHDI Kendari City for Hindus in Kendari City are an increase in and understanding of Sradhha and Bhakti about the teachings of the religion they adhere to. Keywords: Communication Strategy, Parisada Hindu Dharma Indonesia, Development of Hindus